Moving beyond local practice: Reconfiguring the adoption of a breast cancer diagnostic technology. (April 2015) - Maniatopoulos, Gregory; Procter, Rob; Llewellyn, Sue; Harvey, Gill; Boyd, Alan
Abstract: This paper explores the ways in which technological innovation becomes adopted and incorporated into healthcare practice. Drawing upon the notion of 'field of practices', we examine how adoption is subject to spatially and temporally distributed reconfigurations across a multi-level set of practices, ranging from the policy level to the micro-level setting of individual action. The empirical backdrop is provided by a case study of the adoption of Breast Lymph Node Assay (BLNA), a diagnostic technology innovation for the treatment of breast cancer patients. Our aim is to contribute to the development of a more comprehensive analysis of the processes surrounding the adoption and incorporation of complex healthcare technologies into routine practice. Highlights: We explore the ways in which a breast cancer diagnostic technology becomes adopted. We identify reconfigurations across a multi-level set of practices. Reconfigurations are not always easy to implement or even identify a priori. Unsuccessful reconfiguration processes could become a barrier to technology adoption.